2014
DOI: 10.1186/1752-1947-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Fulminant systemic capillary leak syndrome due to C1 inhibitor deficiency complicating acute dermatomyositis: a case report

Abstract: IntroductionDermatomyositis is a chronic inflammatory disorder characterized by muscular and dermatologic symptoms with variable internal organ involvement. This is the first report on a patient with acute dermatomyositis and fulminant systemic capillary leak syndrome.Case presentationA 69-year-old Caucasian woman with chronic dermatomyositis presented with clinical signs of severe hypovolemic shock and pronounced hemoconcentration (hematocrit, 69%). Her colloid osmotic pressure was 4.6mmHg. Following a bolus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Gradwohl‐Matis et al. reported that a C1 inhibitor deficiency caused an acute combined systolic and diastolic heart failure due to systemic capillary leakage . Therefore, it is possible that low levels of C1 inhibitor may have been associated with acute diastolic dysfunction in our case.…”
Section: Discussionmentioning
confidence: 75%
“…Gradwohl‐Matis et al. reported that a C1 inhibitor deficiency caused an acute combined systolic and diastolic heart failure due to systemic capillary leakage . Therefore, it is possible that low levels of C1 inhibitor may have been associated with acute diastolic dysfunction in our case.…”
Section: Discussionmentioning
confidence: 75%
“…Both hereditary angioedema (HAE) and acquired angioedema (AAE) with C1 inhibitor deficiency have previously been reported in patients with dermatomyositis 31,32 . Although the cause and effect relationship between C1 inhibitor deficiency and dermatomyositis is not clear, C1 inhibitor deficiency will result in loss of inhibition of the classical complement pathway, leading to low serum C4 levels as a result of excessive consumption, and an activated complement system can induce inflammatory myopathy by deposition of the membrane attack complex in muscle tissues 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Both hereditary angioedema (HAE) and acquired angioedema (AAE) with C1 inhibitor deficiency have previously been reported in patients with dermatomyositis. 31,32 Although the cause and effect…”
Section: Discussionmentioning
confidence: 99%
“…In Kakogawa et al study an elevated level of serum prolactin was found, as the 16-kDa cleavage product of prolactin as well as C1 inhibitor deficiency is a major contributor to PPCM [8,10]. The deficiency of C1 inhibitor led to the onset of acute heart failure, marked by a combined dysfunction in both systolic and diastolic phases, attributed to the leakage of capillaries throughout the body [11]. However, we are unable to test serum prolactin and C1 inhibitor due to limited resources and unavailability of test in peripheral setting.…”
Section: [Case Presentation]mentioning
confidence: 94%